The Extinctionist Man - Makia, Ahmad (Identities: Journal for Politics, Gender and Culture, 2022)
This essay explores how critical necropolitical frameworks bring to light, not only exploited subjugation, but the quality of doom, destruction and collapse embedded in masculine expression. It elaborates on how the proto-patriarchal view of death, or more accurately the prospective view towards it, emerges from a skewed narrative fixture, in which ‘life’ is determined by what it isn’t, ‘death.’ Similar to the dissociative and occultive schisms in the patriarchal rationale of life forms, such as the opposition of ‘man’ to ‘woman’ or ‘human’ to ‘animal,’ the concept of death is realized into an abject non-place inhabited by subjectivities of “fucking” and “killing.” Puncturing this staging of ‘alive’ patriarchal function, the necropolitical presents the condition of death as a possible flourishing identity and an already-present frontier of human expression, where ‘life’ and ‘death’ aren’t separate entities to one another but enmeshed, as if in masquerade of one another. The essay also provides critique and caution on how fiction and theory transpire into ‘staged’ realities, especially in the manifestation of the abject body. Its concluding remarks support the inclusion of “straightness” in fluid sexual discourse by highlighting how the appropriation and possession of traditional and existing social roles, rather than only those in defiance or at their fringe, has birthed the concepts of kineticism and fluidity in sexual expression. Author(s): Ahmad Makia Title (English): The Extinctionist Man Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 92-106 Page Count: 14 Citation (English): Ahmad Makia, "The Extinctionist Man,” Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022): 92-106. Author Biography Ahmad Makia, Independent Researcher Ahmad Makia is a writer and publisher from the United Arab Emirates. He currently operates under the publishing alias HOUSE and heads the publications department of the Sharjah Art Foundation